Analisis Efektivitas Penggunaan Teknologi dalam Pendidikan Terhadap Peningkatan Hasil Belajar - Suyuti Suyuti; Paulina Maria Ekasari Wahyuningrum; M. Abdun Jamil; Muhammad Latif Nawawi; Donny Aditia; Ni Gusti Ayu Lia Rusmayani (Departement of Mathematics Education, 2023)
This research aims to analyze the effectiveness of technology use in education on improving students' learning outcomes. The research method used is literature review by collecting data from various sources related to the use of technology in education. The results of the study indicate that the use of technology in education can significantly improve students' learning outcomes, especially in developing cognitive skills and critical thinking. In addition, technology can also help improve the efficiency and effectiveness of the learning process. However, the use of technology in education also has challenges and risks that must be well managed. Therefore, the use of technology in education must be carefully selected and integrated to achieve optimal results.